PENGARUH PENGGUNAAN MEDIA VIDEO TUTORIAL DAN MOTIVASITERHADAP HASIL BELAJAR SISWA MATA PELAJARAN SENI BUDAYA SUB SENI RUPA DI KELAS VII SMPN 23 PADANG - Rizki Brakah Binauvan, Drs. Suib Awrus, M.Pd. (Universitas Negeri Padang, 2019)
This0study aims to4determineTthe comparisonPof learning outcomes of fine art student who have highHmotivationJandLlowBmotivationMwhoMare taught with video tutorial media and conventional media. This study uses quasi-experimental methods with a 2 x 2 design form. For its implementation, the first researcher conducted a motivation test on the second class, the second conducted a test of initial knowledge and final knowledge. TheVresultsVofVthisVstudyVare: studentsPwho are taughtPusingPvideoKtutorialLmedia, learningPoutcomes are better than studentsZwho are taughtPusing conventional media. For thatKthe use ofJvideoJtutorialKmedia is good and good to be applied to students who have hightmotivation and lowymotivation in learning fine art in class VII SMPN 23 Padang.Keywords : video tutorial media, motivation, learning outcomes